(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In this article, the inheritance of quantitative traits in F1 hybrid combinations exhibited various patterns, including absence of dominance, intermediate, complete, and overdominance. The inheritance of the abovementioned quantitative traits indicated that they possess a polygenic nature.